Impact of Smoking on Oxygen Saturation, Carboxyhemoglobin, and Carbon Monoxide Levels: A Pilot Study of Chairside Biomarkers for Smoking Status - Christeena Binny; Mathew Jacob; Saramma M. Fenn (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Tobacco use is associated with various health risks, including respiratory and cardiovascular diseases. Aim: The objective of this study is to assess the levels of oxygen saturation, carboxyhemoglobin, and carbon monoxide in smokers compared to nonsmokers. Methods: Participants who had refrained from smoking for 3 hours prior to measuring exhaled carbon monoxide and carboxyhemoglobin levels. After holding their breath for 15 s, they exhaled into a breath analyzer, which displayed carbon monoxide (ppm) and carboxyhemoglobin levels (%). Oxygen saturation was measured with a pulse oximeter on the right index finger. Results: Significant differences were found in carbon monoxide and carboxyhemoglobin levels between cigarette smokers and Beedi smokers as well as between cigarette smokers and nonsmokers (P = 0.001). Beedi smokers also showed higher levels than nonsmokers (P = 0.001). Using ANOVA, differences in these levels across the groups (P = 0.001) were observed. Correlation analysis showed positive associations between carbon monoxide and carboxyhemoglobin and negative correlations between oxygen saturation and these parameters. Carboxyhemoglobin was significantly correlated with both carbon monoxide and oxygen saturation. Conclusion: The findings indicate that oxygen saturation, carboxyhemoglobin, and carbon monoxide levels are effective chairside biomarkers of smoking status, offering smokers immediate feedback on the harmful effects of smoking.